Dual Role of Lithium on the Structure and Self-Healing Ability of PMMA-Silica Coatings on AA7075 Alloy - Trentin, Andressa [UNESP]; Harb, Samarah V. [UNESP]; Uvida, Mayara C. [UNESP]; Pulcinelli, Sandra H. [UNESP]; Santilli, Celso V. [UNESP]; Marcoen, Kristof; Pletincx, Sven; Terryn, Herman; Hauffman, Tom; Hammer, Peter [UNESP] (American Chemical Society (ACS), 2019)
In this work, structural and active corrosion inhibition effects induced by lithium ion addition in organic-inorganic coatings based on poly(methyl methacrylate) (PMMA)-silica sol-gel coatings have been investigated. The addition of increasing amounts of lithium carbonate (0, 500, 1000, and 2000 ppm), yielded homogeneous hybrid coatings with increased connectivity of nanometric silica cross-link nodes, covalently linked to the PMMA matrix, and improved adhesion to the aluminum substrate (AA7075). Electrochemical impedance spectroscopy (EIS), performed in 3.5% NaCl aqueous solution, showed that the improved structural properties of coatings with higher lithium loadings result in an increased corrosion resistance, with an impedance modulus up to 50 Gω cm2, and revealed that the lithium induced self-healing ability significantly improves their durability. Time-of-flight secondary ion mass spectrometry (ToF-SIMS) and X-ray photoelectron spectroscopy (XPS) suggest that the regeneration process occurs by means of lithium ions leaching from the adjacent coating toward the corrosion spot, which is restored by a protective layer of precipitated Li rich aluminum hydroxide species. An analogue mechanism has been proposed for artificially scratched coatings presenting an increase of the impedance modulus after salt spray test compared to the lithium free coating. These results evidence the active role of lithium ions in improving the passive barrier of the PMMA-silica coating and in providing through the self-restoring ability a significantly extended service life of AA7075 alloy exposed to saline environment.
Keywords: aluminum alloy; corrosion inhibition; lithium carbonate; PMMA-silica hybrid; self-healing